The Provenance of the Pseudepigrapha : Jewish, Christian, or Other? - Davila, James (Supplements to the Journal for the Study of Judaism, 2005)
The Old Testament pseudepigrapha are ancient quasi-biblical texts inspired by the Hebrew Bible. Although frequently mined as Jewish background by New Testament specialists, they were transmitted almost entirely in Christian circles, often only in translation. Christian authors wrote some pseudepigrapha and did not necessarily always mention explicitly Christian topics. This book challenges the assumption that pseudepigrapha are Jewish compositions until proven otherwise. It proposes a methodology for understanding them first in the social context of their earliest manuscripts, inferring still earlier origins only as required by positive evidence while considering the full range of possible authors (Jews, Christians, "God-fearers," Samaritans, etc.). It analyzes a substantial corpus of pseudepigrapha, distinguishing those that are probably Jewish from those of more doubtful origins.